2017
DOI: 10.1080/09540121.2017.1307916
|View full text |Cite
|
Sign up to set email alerts
|

Change in patterns of HIV status disclosure in the HAART era and association of HIV status disclosure with depression level among women

Abstract: Whether widespread use of HAART changed patterns of HIV status disclosure among women living with HIV is largely unknown. In addition, the association between time to first HIV disclosure and depression has not been fully explored among women. A retrospective cross-sectional survey was conducted among HIV-infected women from the Washington, DC site of the Women’s Interagency HIV Study to collect detailed information about their HIV status disclosure behavior. A sample of 202 HIV-positive women, 102 diagnosed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…betrayal) [ 8 , 15 , 24 26 ]. Other studies showed that delayed disclosure was attributable to fear of early stigmatization before the symptoms appeared because of the effectiveness of ARVs in concealing symptoms [ 13 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…betrayal) [ 8 , 15 , 24 26 ]. Other studies showed that delayed disclosure was attributable to fear of early stigmatization before the symptoms appeared because of the effectiveness of ARVs in concealing symptoms [ 13 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…56 As a result of nondisclosure, HIV-infected individuals may feel less support or the need to hide this significant area of their lives, thereby diminishing the quality of support, and increasing their vulnerability to depression. 35 Future research should evaluate concerns regarding disclosure and/or reactions to disclosure and its association with perceived social support, and promote targeted interventions to treat depression that focus on enhancing communication and disclosure to stimulate social support. Interpersonal therapy, for instance, is aimed at targeting interpersonal conflict or situations as well as at increasing individuals’ social networks, thereby improving the quality of interpersonal relationships or circumstances, specifically, those linked to current depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 For instance, decreased social support among individuals with HIV may result from both perceived stigma and nondisclosure of HIV status, 32,33 which may be exacerbated by limitations to illness-associated social support, 34 increasing depressive symptoms. 35 Given that CT has been linked to reduced levels of social support, smaller social networks, and interpersonal dysfunction, 16 the combination of CT and HIV may result in significantly greater levels of depression that are not mitigated by social support, as this additive or synergistic effect may require greater levels of support in order to be protective. Therefore, it is possible that even among HIV-infected individuals with higher levels of social support, the synergy of CT, HIV infection, and depression may thwart the protective benefit of social support.…”
Section: Introductionmentioning
confidence: 99%
“…However, Kiene et al found that depressive symptoms were associated with HIV disclosure behavior among adult Ugandan men and women, but this relationship was dependent on time since diagnosis [11]. Another study found that a longer time to first HIV disclosure, but not extent of disclosure was associated with depression among women from the Women's Interagency HIV Study in Washington, D.C. [14].…”
Section: Depressive Symptoms and Hiv Disclosure Behaviormentioning
confidence: 99%
“…Nevertheless, Cook and colleagues did not find statistically significant correlations between depressive symptoms and any type of HIV disclosure (to a sex/romantic partner, family member or friend/other person) among young MSM aged 12 to 24 using data from the Adolescent Trials Network [12]. Other studies have shown that depressive symptoms were negatively associated with disclosure self-efficacy and HIV disclosure to partners among newly diagnosed MSM in New York City [13], and that time to first disclosure of HIV status was positively associated with depression among women living with HIV in Washington, D.C. [14]. Based on these findings, depressive symptoms may be negatively associated with disclosure to sexual partners among men and women in the current study population.…”
Section: Introductionmentioning
confidence: 99%